The summer we found the baby - Hest, Amy (Candlewick Press, 2020)
Eleven-year-old Julie Sweet never could have imagined how her life would change the morning she and her sister, Martha, find an abandoned baby at the new children's library in Belle Beach, Long Island. Twelve-year-old Bruno Ben-Eli is heading out on an important errand for his brother when he discovers Julie, Martha, and the baby. The children soon learn the truth about the baby is more complicated than they ever imagined.